1990
DOI: 10.1002/mcs.1220020309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of injection systems for open tubular liquid chromatography

Abstract: Abstract. The main advantages of open tubular liquid chromatography (OTLC) over conventional packed-column liquid chromatography are the gain in resolution and the increased permeability. At present the reproducible preparation of narrow-bore columns and the lack of suitable commercial chromatographic equipment delay the development of OTLC. There are stringent requirements for injectors and detectors for OTLC with respect to their volumes, geometry, and contributions to the total band broadening. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…( 3) still provides a convenient representation of the minimal amount of hydrodynamic dispersion all injected peaks have been subjected to (V 2 ,inj,hydro) as well as of the variance contribution that increases with increasing injection volume (V 2 ,inj,vol). A similar differentiation between those two contributions was made by Claessens et al when investigating injection systems for open-tubular liquid chromatography [29], for normal and narrow bore column HPLC by Coq et al Coq [30] and Sanchez et al [31].…”
Section: Introductionmentioning
confidence: 53%
“…( 3) still provides a convenient representation of the minimal amount of hydrodynamic dispersion all injected peaks have been subjected to (V 2 ,inj,hydro) as well as of the variance contribution that increases with increasing injection volume (V 2 ,inj,vol). A similar differentiation between those two contributions was made by Claessens et al when investigating injection systems for open-tubular liquid chromatography [29], for normal and narrow bore column HPLC by Coq et al Coq [30] and Sanchez et al [31].…”
Section: Introductionmentioning
confidence: 53%
“…Previous studies of injector design have shown that a good injection requires a narrow, low-volume plug of sample with no poorly swept flow paths [20,53,[58][59][60][61][62], which are explained more in the next section.…”
Section: Injector Contributionsmentioning
confidence: 99%
“…Normalmente, tais volumes de injeção podem ser atingidos facilmente e com grande repetibilidade, utilizando válvulas comercialmente disponíveis. Caso se necessite de volumes de injeção menores que aqueles fornecidos pelas válvulas, pode-se empregar diversas técnicas de injeção descritas na literatura [59][60][61][62] . Atualmente, válvulas de até 4 nL podem ser encontradas comercialmente.…”
Section: Dispositivos De Introdução Da Amostraunclassified